Teaching History in Schools in Chita in Context of Implementation of Tasks of the Soviet State in Sphere of Historical Policy (late 1930-ies - early 1940-ies) - O. A. Yaremchuk (Научный диалог, 2017)
The article analyzes the specifics of teaching history in schools of Chita in the late 1930-ies - early 1940-ies. The sources were published party and government documents and correspondence from the collections of the State archive of the Transbaikal region, introduced into scientific circulation for the first time. It is shown that the pre-war years was a very important step for the development of school historical education in our country, which determined changes in the content of this discipline and methods of its learning. Special attention in research is paid to the peculiarities of organization of educational process on the lessons of history, the characteristics of personnel and material support of the Chita schools. The author dwells on the problems of realization of educational process on the subject, among which there are shortage of qualified personnel, lack of necessary educational and methodical literature, presence of students behind the school program, and others. It is noted that due to the remoteness of the Chita region from the center the solution of these questions objectively was slower. However, despite the shortcomings of the efforts of the education department, school administrators and all teachers of Chita gradually contributed to bringing the quality of the teaching of history in conformity with the essential requirements.